Alternativas de soluciones viales en el sector Martha de Roldós, Guayaquil - Peñafiel Sánchez, Richard Omar (2024)
This titling project addresses traffic congestion in the Martha Bucaram sector of Roldós, Guayaquil, highlighting how demographic growth and the lack of adequate road infrastructure have generated an environment with limited mobility, affecting both residents and commercial activities. The lack of maintenance and urban planning has aggravated the situation, leading to road saturation and access problems. The approach to the problem underlines the urgent need for road solutions that improve mobility and quality of life in the area. A technical evaluation of design alternatives to improve vehicular and pedestrian mobility is proposed, with specific objectives focused on diagnosing the current situation, collecting technical data, and proposing solutions based on mobility criteria. The central idea is that the implementation of control measures and road proposals, based on technical studies, would have a positive impact on traffic management in Martha de Roldós.